PERLINDUNGAN HUKUM SATUAN POLISI PAMONG PRAJA DALAM PELAKSANAAN TUGAS PENEGAKAN PERATURAN DAERAH DI KABUPATEN KUTAI KARTANEGARA - Muhammad Ruchiyat Reynaldi (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT Public order is an important step in the success of ongoing development. For this reason, the government of Kutai Kartanegara Regency needs to issue a policy that can confirm the issue of public order in accordance with the current conditions of Kutai Kartanegara Regency. For this reason, policies in the form of Regional Regulations are made which are expected to become legal rules in overcoming problems of public order, as well as institutions or apparatuses that can assist Regional Heads in enforcing regional regulations and Regional Head Decrees, as well as implementing peace and public order in Kutai Kartanegara Regency. The first problem formulation is how the work procedure for enforcing Regional Regulations at the Satpol PP Kutai Kartanegara, the second, what are the steps taken by the Satpol PP if in carrying out a task there is a lawsuit. The type of research that the author uses is empirical juridical research, which is a type of empirical juridical research, or what is called field research, which examines the applicable legal provisions and what happens in reality in society. The results of the study state that the procedures for enforcing Regional Regulations at Satpol PP Kutai Kartanegara are conducting directives to the public and legal entities that violate Regional Regulations, providing guidance and / or socialization to the public and legal entities, non-judicial preventive action. and the steps taken by the Satpol PP if the Satpol PP in carrying out the duties of the lawsuit is the Satpol PP in the case of the demands making confirmation to the authorities (police) in the event that the incident is in accordance with the chronology, In an effort to confirm to the authorities (Police) Satpol PP is waiting a decision from the police regarding the investigation, whether the case is a serious, moderate or minor crime, with the examination of the reported party and the reporter within 2x24 hours and if there is a lawsuit, the attorney is from the legal department. Keywords : Enforcement, Public Order